PERSEPSI MAHASISWA TERHADAP PEMBELAJARAN BLENDED BERHUBUNGAN DENGAN PENINGKATAN HASIL BELAJAR - Rasita Purba; Lelly Fridiarty; Adikahriani .; Risti Rosmiati; Fatma Tresno Ingtyas (JURNAL PENELITIAN BIDANG PENDIDIKAN, 2022)
Nutritional counseling is an essential component of nutrition students to be equipped to address nutritional problems. The objective of the study was to analyze the correlation of nutrition students for teaching presence perception in blended learning to improve the learning outcomes of nutritional counseling stages. The study used a cross-sectional research design, nutrition students in nutritional counseling courses completed the 13-item Community of Inquiry (COI) questionnaire for teaching presence. The results showed that students had higher agreement across the level of teaching presence. The findings of this study suggest that perceived teaching presence was significantly related to improving the learning outcomes of nutritional counseling stages.